Time Allocation and the Economic Role of Peasant Farm Women of Thenmaradchi Area, Jaffna District - Umashankar, K.; Abirami, R. (Vavuniya Campus of the University of Jaffna, 2011)
This research has taken effort to identify the determinants and quantify the effect of these determinants on the participation decision of the Thenmaradchi peasant farm women in both on-farm and non-farm activities. Thenmaradchi is one of the potential areas for agricultural production in the Jaffna district. But, mostly the income from the farming tends to declining even below the subsistence level. The ground situation became worse due to the civil disturbances prevailed in the near past. Nevertheless farming has been a major source of the household income, where labor force seems to be the only rich source those poor households' possess. But there exists a market for labor so that farm households are able to work in and hire out labor at a given market wage. Out of 1747 farm households in the study area 198 farm households were selected by using simple random sampling method. The data were collected by administering a structured questionnaire. The collected data were analyzed within the frame work of probit regression model. The estimated coefficient of women' age manifested a positive influence over the possibility of their involvement in farming at 10% significant level. This implies that when woman's age is increased by one year, the probability of her decision to participate in the on-farm activities arises by 1.42%. Meanwhile the variable access to tarred road facility available to the village exerted a negative impact on the women's participation decision on on-farm work. The variable was found to be highly significant at 1% level, hence it can be concluded that, if tarred road facility is available to the village, the probability of the farm work participation of the women decreases by 0.01%. Same time access to the subsidy also influenced negatively on the on-farm working decision at 1% significant level. This implies that, if subsidy facility is available to the farm households, the probability of participating decision of women in the on-farm activities will decrease by 0.025%. It can be suggested that if the subsidy for farm input is available, the farm operators may be hire- in more labor and there is less requirement for the women to get involved in farm activities Because in most instance peasant woman works at their own farm to substitute the hired labor with the intention of cutting down the cost of production. Paradoxically access to the tarred road positively influences on the probability of the peasant women's non-farm activities at 5% significant level. This implies that, if the tarred road facility is available, the probability of the non-farm work participation decision of the women will go up by 4.56%. Practically, it is true because when infrastructure facilities are available to the farm households that will expect to increase their mobility out of their farms. Therefore, it is explicit that, extending the labor market opportunities to the rural areas, well constructed road facilities and regular public transportation facilities may be enhancing the non-farm labor participation decision of Thenmaradchi peasant women.
Keywords: Peasant women; On-farm working decisions; Non-farm working decisions; Profit